Alegro-me em ver o outro sofrer? uma descrição do vocabulário emocional e das expressões faciais da Schadenfreude - Assis, Vanessa Andrade de (2025)
Schadenfreude is a secondary emotion, defined as a specific and atypical type of joy at the suffering of others. Despite its social and psychological relevance, there is still little research on this emotion, especially in the national context and in the field of psychology. In Brazil, Schadenfreude lacks a clear and culturally recognized nomenclature, which makes it difficult to identify linguistically. In addition, it is a socially undesirable emotion, often biased in reports due to social convenience. Our study sought to fill these gaps by investigating both the naming and identification of Schadenfreude under conditions of bias. Data collection took place at CEPITEC, with students from the Federal University of Sergipe. Participants were interviewed in controlled situations, with webcam video recordings. The interviews were transcribed using ELAN software, and a sentiment analysis was applied to specific excerpts of the responses related to negative situations, to identify the polarity of the words associated with the expression of Schadenfreude. The results showed that participants use a variety of emotional terms to describe situations involving Schadenfreude, although the absence of a specific terminology is still evident. The analysis of feelings revealed that the vocabulary associated with this emotion contains terms with positive and negative polarities, which coexist in all the situations analyzed. These findings reinforce the hypothesis that Schadenfreude emerges from the combination of these emotional polarities. In addition, the participants' facial expressions were analyzed using OpenFace software. The data indicated the presence of movements characteristic of Action Units (AUs) associated with joy, such as AU6 (contraction of the muscles around the eyes) and AU12 (raising the corners of the lips). However, these activations were more intense in situations that evoked Schadenfreude, compared to situations of pure joy. These findings highlight the relationship between the linguistic and gestural components of Schadenfreude, pointing to the importance of integrating quantitative and automated analyses in the study of this emotion. The research contributes to the advancement of the understanding of how Schadenfreude manifests itself in Brazil through linguistic and gestural expressions, offering subsidies for the development of more precise and culturally adjusted methodologies for its analysis.